2022
DOI: 10.1332/204378921x16315375796362
|View full text |Cite
|
Sign up to set email alerts
|

Aboriginal social housing in remote Australia: crowded, unrepaired and raising the risk of infectious diseases

Abstract: Sufficient, well-maintained housing infrastructure can support healthy living practices for hygiene, safety and nutrition. This article focuses on the relationship between housing and health through a case study in the remote Barkly region in the Northern Territory, Australia. A research partnership between Anyinginyi Health Aboriginal Corporation and academic researchers employed a mixed methodological approach, involving interviews with residents, clinical and outreach staff, and clinical database analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Healthcare delivery in prisons can be costly and unsafe because the inmates often need to be transported to medical centers for comprehensive examination and treatment. Several methods and interventions, such as early screening, early treatment, balanced nutrition, reduction of overcrowding, and use of remote diagnostic systems and networks, can help decrease the occurrence and transmission of diseases [ 27 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare delivery in prisons can be costly and unsafe because the inmates often need to be transported to medical centers for comprehensive examination and treatment. Several methods and interventions, such as early screening, early treatment, balanced nutrition, reduction of overcrowding, and use of remote diagnostic systems and networks, can help decrease the occurrence and transmission of diseases [ 27 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although not statistically significant, there were more surgical retrievals in warmer weather in the humid zone. Remote communities in the NT experience high rates of soft tissue infections, which can be exacerbated by hot weather conditions [24]. Overcrowded housing due to extreme environmental heat forces people to congregate, increasing the risk of infectious diseases such as scabies, streptococcus, and staphylococcus [2,25].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, comprehensive policy measures addressing education, employment, and land rights are necessary to considerably enhance the housing conditions and general welfare of Malaysia's indigenous communities. Studies have indicated that through resolving health concerns, encouraging dietary consumption, and raising perceptions of safety, better housing infrastructure is crucial to enhancing well-being (Memmott et al, 2022). Memmott and colleagues, 2022).…”
Section: Introductionmentioning
confidence: 99%